Saberes construídos pelos professores de matemática em sua prática docente na educação de jovens e adultos - CORÔA, Renata Paixão (2006)
This work is about the teachers practice of mathematics developed in a special program of Brazilian young and adult education called EJA. I aim to investigate that teaching practice in a way of quality research in order to highlight the knowledge produced by the teaching experience process in EJA, based upon what the Math teachers say. For collecting data the instruments used were a kind of interview with Math teachers and a questionnaire to 48 students of a public school in BRAZIL Belem City State of Para. From the answers of the subjects teachers and students - emerged the knowledge produced by the teachers in their teaching experience processes. Some categories of analysis include field experience knowledge regarding the adequate language and methodology to students, the contextualization of the Math contents, the students historical social experiences as citizens, among others. Throughout their teaching experiences, teachers can reelaborate and adapt the vast knowledge due to the peculiarities of the Math students in EJA and of their own experience by reflection. What the Math teachers say means as evidences of their dissatisfaction with the kind of information and orientation received along their initial education professional process disregarding the EJA special teaching. So, I could find it is important that teachers establish partnership relationship in order to reach better results in the teaching for the students of EJA. More over, that can serve as a contribution to the implement and improvement of Political Pedagogic Education Projects realized by the schools in EJA classes.